RAGAM POLA TABUHAN TAHAR PADA KESENIAN RADAT YA MUHAMMAD DI DUSUN SEBADI KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Dazulli, M.; Syahrani, Agus; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The various percussion patterns of Ya Muhammad radat was the background in this research. The problem formulations in this research were how to play tahar, how many varieties of its percussion pattern, and how the various percussion pattern Ya Muhammad radat in Sebadi Village, Teluk Keramat Subdistrict, Sambas Regency.The method used in this research was descriptive method with qualitative research and musicology approach. Sources of data in this research was a person who understands and knows about the variety percussion pattern Ya Muhammad radat in Sebadi Village, Teluk Keramat Subdistrict, Sambas Regency. Data collection techniques in this research were observation, interviews, and documentation with researchers as the main instrument. Checking the validity of data in this research using extension of observation and triangulation technique. Data analysis techniques were analysis during data collection and analysis after data collection. The results of this research were there are three kinds of percussion pattern of Ya Muhammad radat in Sebadi Village, Teluk Keramat Subdistrict, Sambas Regency which functioned as dance accompaniment music consisting of dance and music, which are ngambek, nyaut, and ribu-ribu. This research described all kind of those pattern. Each of them uses literal repetition and 4/4 time signature. Tahar of Ya Muhammad radat has two timbre, those are